Strengthening local economy: An example of higher education institutions' engagement in "co-creation for sustainability" - Anna Bogedain; Rüdiger Hamm (REGION, 2020)
Major societal challenges like energy efficiency, climate change and resource scarcity trigger and influence continuous change processes worldwide, nationwide, but also on all regional levels. They force regions to think about (a more) sustainable development. As the transformation processes necessary for sustainable development are complex there is a need for actors willing to engage and support sustainability transitions. Higher education institutions (HEIs) are often expected to be one of these supporters on the regional level. The central aim of this paper is to show by the use of an example, that HEIs are able to provide impulses for sustainable transformation. Following Pflitsch and Radinger-Peer (2018:918) HEIs can play different roles in regional sustainable transition; the authors use two dimensions to distinguish these roles - depth and autonomy: - As to depth HEIs' roles can be "comprehensive, involving diverse actors and approaching sustainability with a holistic perspective" or "more fragmented and passive, but also more focused on specific topics". - As to autonomy the roles can be "autonomous, the university defining its own focus and priorities through interacting with a broad range of regional actors" or "more directed, the university working on topics that are relevant from the perspective of the regional or federal-state government". Using this rough classification the HEI in our example focuses on a "specific topic" and it is interacting with other regional respectively local actors on a topic that is not only relevant from the perspective of most German cities and their citizens but also from the national and federal government's perspective. The paper starts with a short systemisation of transfer channels and missions of HEIs. It starts with a description of transfer channels used by the two traditional missions of HEIs - education and research. Afterwards the concept of "third mission" is introduced and distinguished from a possible fourth mission of HEIs - the concept of "co-creation for sustainability". Afterwards it deals with important concepts and approaches which are characteristic elements of "co-creation for sustainability" - transformative research, participatory action research (PAR), urban living labs and student service learning. The "specific topic" that serves as an example is introduced after that: it is about the problem of local economy in urban neighbourhoods. Local economy will be defined, its problems resulting from the functional change of urban neighbourhoods are sketched and the arising necessity of strengthening local economies will be discussed. We show the methodological concept that is used to develop strategies and specific measures for strengthening local economy. The paper shows that the elements of this concept are typical approaches of transformative sciences. Afterwards concrete examples stemming from an urban neighbourhood which is part of the city of Viersen (Northrhine-Westphalia, Germany) is used to show, how the approach works in practise. The paper ends trying to explain, why projects like this give an example of HEIs' impulses for sustainable development in their regional surrounding. Furthermore, the usefulness, but also the shortcomings and further research necessities of the approach will be discussed.
Keywords: 330